Zur Bedeutung des Begriffes wḥm - Kootz, Anja (AAeO - Afrikanistik-Aegyptologie-Online, 2019)
The references of the term wḥm suggest a new interpretation of the semantics, as the usual translation ‚repeat; report (in the sense of ‚repeat a message’)’ seldom contributes to an understanding of the text’s content. With the aid of numerous examples from different sources and times it will be demonstrated that a translation using ‚(re-)activating, realise, manifest; execute, perform; as well as implement, enforce’ seems to be more appropriate in relation to the core of the term wḥm; i.e. the agens of an action must not be the cause or initiator by itself. It might be only the performer (executive) of an action planned or induced by another. It is about the reactivation of a destruction and the activation of derelict matter. It is also about the realisation of an idea or the execution of an order/ command and finally about the enforcement of a potential.